Pelatihan dan pendampingan digital marketing di PT. Dwi Elang Perkasa - Meyliana, Anastasia; Andriani, Anik; Safitri, Lina Ayu; Rapiyanta, Paulus Tofan (Nur Science Institute, 2024)
This community service activity aims to improve the ability of business actors to utilize digital technology for marketing and managing websites. This training and mentoring was carried out in response to the challenges of the growing digital era, where more than conventional marketing is needed to reach a broader and more diverse market. The training focuses on two main aspects: first, digital marketing strategies, which include the use of social media, email marketing, SEO (Search Engine Optimization), and paid advertising on digital platforms. Second is website management, which includes website creation and maintenance, exciting content, and analytics to monitor website performance. The methodology used in this activity is a participatory approach, where participants are given theoretical and practical training material. Intensive mentoring sessions were also held to help participants apply the knowledge they have gained into actual practice in their business. This activity significantly increased participants' understanding and skills in digital marketing and website management. Participants can manage their websites and design and execute effective digital marketing campaigns. This activity is expected to increase the competitiveness and sustainability of small and medium businesses in the digital era.